Rancang Bangun Prototype Smart Home System Kontrol Lokal Area Menggunakan IoT MQTT Panel - Ilham Gunawan Mardianto; Aditya Chandra H; Widi Ariwibowo; Mahendra Widyartono (Politeknik Kampar, 2023)
With the progress of civilization, science, and technology in Indonesia, the study entitled